Faktor-Faktor Yang Berpengaruh Terhadap Pendapatan Petani Jeruk Di Junrejo Kota Batu - Anna Ismawati; Cakti Indra Gunawan; Eri Yusnita Arvianti (Ecobuss, 2023)
This study aims to determine several factors that influence the income of citrus farmers in Junrejo District, Batu City. The research method used is quantitative, with data collection methods in the form of observation, documentation and questionnaires. From the results of multiple regression data processing, it shows that the factors that have a positive and significant effect in this study are farmer capital and labour (farming workers), while the length of farming does not significantly influence the increase in citrus farmer income in Junrejo District, Batu City. Thus, the length of business cannot guarantee an increase in the income of citrus farmers in Junrejo District, Batu City, which is dominant, namely farmer capital. Keywords: Income, Citrus Farmer, Batu City